The Emerging Role of Carbon-Ion Radiotherapy - Ebner, Daniel K.; Kamada, Tadashi (Frontiers in Oncology, 2016)
Carbon-ion radiotherapy (CIRT) has progressed rapidly in technological delivery, indications, and efficacy. Owing to a focused dose distribution in addition to high linear energy transfer and subsequently high relative biological effect, CIRT is uniquely able to target otherwise untreatable hypoxic and radioresistant disease, while opening the door for substantially hypofractionated treatment of normal and radiosensitive disease. CIRT has increasingly garnered international attention, and is nearing the tipping point for international adoption.